ANALISIS DAN PERANCANGAN JARINGAN DUAL STACK SEBAGAI METODE TRANSISI IPv4 KE IPv6 - Anita, Merlie; Raharjo, Suwanto; Sholeh, Muhammad (Jurnal Jarkom, 2014)
ABSTRACTIPv6 present as IPv4 replacement with some feature to cover IPv4 weakness. Transition is needed in order to migrate to IPv6 because totally migration will cause much networking problem considering most of network device in this time are still designed for IPv4. Transition method used in this research is dual stack which connected to tunnel broker so that local network can communicate with internet and be able to access IPv6 sites. In dual stack network, host and router implements both IPv4 and IPv6. With these two kind of IP, gateway address must consists of two different addresses either because sending and receiving process from client to server or vice versa is happen in separate way. Dual stack most implemented in a network because its compatibility in network device and it doesnât need necessary to change extremely configuration of IPv4 existing network. As a result from this research, IPv4 network performance has 2% faster for RTT than IPv6 network. For time used and speed transfer using FTP, IPv4 network has 3% faster than IPv6 network. IPv6 network has 10% better performance for throughput than IPv4 does. Whereas jitter, IPv6 has 44% smaller than IPv4. Considering IPv4 limited allocation address nowadays doing the transition to IPv6 using dual stack network is a good choice to deploy IPv6 used.Â Keywords: dual stack, IPv6, tunnel broker